Analisis Keputusan Kpu Nomor 789 Tahun 2024 Tentang Penetapan Daftar Calon Tetap Anggota Dpd Dapil Sumatera Barat Perspektif Siyasah Dusturriyah - Sopian, Sopian; Khalid, Khalid (Legal Standing : Jurnal Ilmu Hukum, 2025)
The purpose of this article aims to clarify the Decree of the General Election Commission (KPU) of the Republic of Indonesia No. 789 of 2024 concerning the Determination of the Permanent Candidate List for DPD RI Members for the Electoral District of West Sumatra Against the Decision of the Constitutional Court No. 03-03 / PHPU.DPD-XXII / 2024 and to clarify the Decree of the KPU RI No. 789 of 2024 in the Perspective of Fiqh Siyasah. . The writing method uses a normative approach and data collection techniques using literature studies. This article is descriptive and aims to solve problems. Based on the analysis, this article found that the KPU RI Decree resulted in a loss of constitutional rights for Irman Gusman to be able to participate in the general election contest for DPD RI Members for the West Sumatra Electoral District. This happened because of the KPU's error in interpreting the PKPU and the Law on Elections. Second, the KPU's non-compliance with the Jakarta PTUN Decision resulted in the law in the DPD RI general election for the West Sumatra electoral district so that Irman Gusman was canceled as a Permanent Candidate List for DPD RI Members in the 2024 General Election. Third, from the perspective of Fiqh Siyasah which includes political rights, it is basically an effort to prevent former candidates from committing the same acts in the future. Fourth, the Constitutional Court's decision to hold a re-vote for the election of DPD RI Members for the West Sumatra Electoral District in the 2024 Election is basically to uphold justice and provide Irman Gusman's Constitutional Rights which have been violated by the cancellation of the KPU RI.